Systematization and codification working operations in the VASTOPOR system** - Todić, Velimir (Journal of Production Engineering, 2023)
In the paper the importance of systematization and codification of working operations of lathing, drilling, milling and grinding for developing of necessary numbers of reliable models of optimization in the VASTOPOR programming system is showen. The significance of developed system of codification working operations for organization the data bank of cutting tools is pointed out as well. This bank is used for technological working process oprimization and projection.